2020
DOI: 10.3892/ol.2020.11588
|View full text |Cite
|
Sign up to set email alerts
|

High KIAA1522 expression predicts a poor prognosis in patients with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly malignant tumor associated with a poor prognosis, and the molecular mechanisms remain poorly understood. KIAA1522 expression is upregulated in various types of tumor tissue; however, its function remains unknown in HCC. Bioinformatics analysis was undertaken using Oncomine, OncoLnc and other databases, in order to determine KIAA1522 expression in HCC and to analyze its association with postoperative prognosis. Reverse transcription-quantitative PCR was performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In order to account for the effects of age and gender on unfavorable outcomes, AFP in serum, univariate, and multivariate analyses were carried out, which suggests that KIAA1522 is a possible prognostic and diagnostic marker. Recent reports [ 14 , 15 ] agree with the findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In order to account for the effects of age and gender on unfavorable outcomes, AFP in serum, univariate, and multivariate analyses were carried out, which suggests that KIAA1522 is a possible prognostic and diagnostic marker. Recent reports [ 14 , 15 ] agree with the findings.…”
Section: Discussionsupporting
confidence: 88%
“…The mRNA expression of KIAA1522 was elevated in a number of malignancies, according to data from the Gene Expression Atlas and The European Bioinformatics Institute databases, which showed that abnormal KIAA1522 expression may have a role in the pathogenesis and growth of cancer [ 13 ]. Recent research demonstrated that elevated KIAA1522 expression accelerated the evolution of HCC by activating the Wnt/ β -catenin pathway and predicted a poor prognosis in HCC patients [ 14 , 15 ]. The function of KIAA1522 in human cancer immunology, however, has hardly ever been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that KIAA1522 was overexpressed in non-small cell lung cancer (NSCLC) and was associated with a poor prognosis in patients with NSCLC [25] . In addition, one study suggested that KIAA1522 might be a novel prognostic marker of hepatocellular carcinoma [26] . Recently, Yi et al.…”
Section: Discussionmentioning
confidence: 99%
“…KIAA1522 is a large protein-coding gene with an uncertain function [23] . It has been reported that the KIAA1522 overexpression has prognostic significance in several cancer types, including CRC [24] , [25] , [26] . Consistently, our earlier findings also suggested that KIAA1522 isa potentialprognostic marker in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the development of surgical resection, liver transplantation, chemotherapy, immunotherapy, and targeted therapy in the therapy of hepatocellular carcinoma, the hepatocellular carcinoma patients’ prognosis is still poor ( Maluccio and Covey, 2012 ; Xu et al, 2020a ). The studies showed that the treatment response and prognosis are influenced by tumor molecular characteristics, although patients own homogeneous clinical risk variables.…”
Section: Discussionmentioning
confidence: 99%